Competition and Performance in the Polish Second Pillar - Rudolph, Heinz; Rocha, Roberto (Washington, DC: World Bank, 2012)
This paper provides an assessment of the Polish funded pension system and the quality of the regulatory framework for the accumulation phase. There are two elements that distinguish the Polish pension fund portfolios from other reforming countries': the relatively high component of domestic equity, and the negligible component on international securities. Although this asset allocation has provided relatively high real rates of return in the past, it may not be the case in the future, as further portfolio diversification to other instruments will become necessary to ensure sustainable rates of return. The paper provides a number of recommendations to expand the opportunities of investments to pension funds. The paper finds that pension fund management companies have been able to exploit scale economies in certain areas of the business, such as collection of revenues, and proposes to study mechanisms to enhance them even more by centralizing also the account management system, which may also help to increase portfolio efficiency and competition. The paper suggests that, with the payout phase starting in 2009, broad definitions in areas such as the role of the public and private sector need to be established. The paper examines products and options that authorities may consider for the design of the payout phase.